2009
DOI: 10.1021/la803409c
|View full text |Cite
|
Sign up to set email alerts
|

Surface Segregation of Fluorinated Moieties on Random Copolymer Films Controlled by Random-Coil Conformation of Polymer Chains in Solution

Abstract: The relationship between solution properties, film-forming methods, and the solid surface structures of random copolymers composed of butyl methacrylate and dodecafluorheptyl methylacrylate (DFHMA) was investigated by contact angle measurements, X-ray photoelectron spectroscopy, sum frequency generation vibrational spectroscopy, and surface tension measurements. The results, based on thermodynamic considerations, demonstrated that the random copolymer chain conformation at the solution/air interface greatly af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 56 publications
1
56
0
2
Order By: Relevance
“…In general, perfluorinated species of fluoropolymers tend to segregate onto the outer surface due to their low surface energies [29,30]. Therefore, fluoropolymers have often been studied as surface-modifying additives of polymer blends, in order to control their surface properties [31].…”
Section: Introductionmentioning
confidence: 99%
“…In general, perfluorinated species of fluoropolymers tend to segregate onto the outer surface due to their low surface energies [29,30]. Therefore, fluoropolymers have often been studied as surface-modifying additives of polymer blends, in order to control their surface properties [31].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and his colleagues studied the surface strucutures of random copolymers composed of methacrylates and fluorinated units solidified from the solution using SFG and other techniques [64][65][66]. It was found that: when the fluorinated unit content was low, the entropic force may dominate the surface structure since the random coil conformation in the solution can greatly affect the final conformation of the copolymer chains at the surface; when the fluorinated unit content was high, the enthalpic force may dominate the surface structure since the fluorinated moieties were prone to segregate to the surface [64].…”
Section: Polymer Surfaces In Air and Surface Restructuring Upon Contamentioning
confidence: 99%
“…It was found that: when the fluorinated unit content was low, the entropic force may dominate the surface structure since the random coil conformation in the solution can greatly affect the final conformation of the copolymer chains at the surface; when the fluorinated unit content was high, the enthalpic force may dominate the surface structure since the fluorinated moieties were prone to segregate to the surface [64]. Besides, the effects of different solvents and the film-forming methods were also discussed [65,66].…”
Section: Polymer Surfaces In Air and Surface Restructuring Upon Contamentioning
confidence: 99%
“…It was reported that the chain shapes or the conformations of polymers in solutions could affect the structures and properties of the polymers in bulk [22,23]. The influence of the preparation methods on the surface properties of fluorinated polymers has been reported in several publications [21,[24][25][26][27][28][29] and it was found that various surface structures can be obtained by controlling film-formation conditions such as the solvent species and preparation methods. When methyl methacrylate (MMA) and 2-perfluorooctylethyl methacrylate (FMA) block copolymer (PMMA-b-PFMA) film was prepared from its micelle solution with PMMA block as micelle corona and PFMA block as 0021-9797/$ -see front matter Ó 2010 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported by our group that a relatively perfect close-packed and well-ordered structure of the perfluoroalkyl side chains at the surface of end-capped poly(methyl methacrylate) film was formed when the film was cast from a benzotrifluoride solution as opposed to being cast from cyclohexanone and toluene solutions [21]. Compared to perfluorinated block polymers [27], a contrary result was obtained when our group investigated the relationship between film-forming methods and the solid surface structure of random copolymers composed of butyl methacrylate (BMA) and dodecafluorheptyl methylacrylate (DFHMA) [24]. The water and paraffin oil contact angles for films by spin coating were higher than those by solution casting.…”
Section: Introductionmentioning
confidence: 99%